Imogen Choi. "The Epic Mirror. Poetry, Conflict Ethics and Political Community in Colonial Peru" - Lara Vilà (Studia Aurea: Revista de Literatura Española y Teoría Literaria del Renacimiento y Siglo de Oro)
Reseña de Imogen Choi. The Epic Mirror. Poetry, Conflict Ethics and Political Community in Colonial Peru, Woodbridge, Tamesis Books, 2022, 229 pp. ISBN 978-1-85566-347-3